‘IT IS UNEASY, AM I READY TO TEACH?': THE PERSPECTIVES OF EFL STUDENTS ON THEIR READINESS IN ONLINE TEACHING PRACTICE - Dwi Arni Margiyanti (Wiralodra English Journal, 2022)
Practicum is a university-based teacher education program that provides prospective teachers with hands-on experience in classroom instruction. Because many of the candidates for teaching positions are not prepared for the rigors of online learning, the transition to online learning has had chaotic consequences for both teachers and students. Unfortunately, several previous studies did not investigated pre-service teachers’ readiness to teach in online practicum. Additionally, the studies examining readiness particularly on foreign language education program through practicum are limited. Therefore, the present study intends to investigate pre-service of foreign language program’s readiness to carry out teaching learning process in online practicum. The study employs a qualitative research methodology. The setting of the study is an oline practicum in a teacher education program in Semarang, Indonesia. The participats of the study are pre-service teachers taking online practicum, estimated 130 participants based on the total population of the department selected. The data collection technique adopts an online open ended survey which is conducted via Google Forms® and synchronous/asynchronous interview. The data collected from questionnaire and interview is then analyzed utilizing a thematic analysis. The results of this research are supposed to contribute practically and pedagogically.